Phytosanitary classification of conventional commercial cacao warehouses - Serôdio, Rogério dos Santos; Prado, Edison Pires do; Abreu, João Manuel de; Campêlo, Anna Maria Freire Luna (Pesquisa Agropecuaria Brasileira, 2014)
As a follow up to the work presented at the last CONBEA (Brazilian Congress of Agricultural Engineering) on grain warehouse (static) classification, based on structural and functional characteristics, the fundamentals of a phytosanitary (dynamic) classification for commercial cacao storage units are developed here. This method of pest control classification is based on the following parameters: 1. The class of warehouse, as a result of the static classification; 2. The prophylactic category, depending upon the hygienic conditions of the unit and upon the preventive and curative treatments used; 3. The entomological infestation category (clear, light, heavy and very heavy), defined by building infestation, sweepings and the stored product; and 4. The fungal contamination category, depending upon the relative humidity of the warehouse environment and upon location, ventilation and moisture characteristics of the building. This study showed the necessity of a sanitary campaign in the storage units, at all levels of the commercial flow of cacao in the region and the necessity for action on the construction of good warehouses, as well as the improvement of existing ones and the use of efficient conservation methods.